Deux figures féminines hors normes de la fin du XIXe siècle – Raoule de Rachilde et Selma de Benedictson - Carlander, Cecilia (Nordlit, 2012)
A year after the French success scandal that Rachilde had with her decadent novel Monsieur Vénus, a novel by the Swedish writer Victoria Benedictsson, Money [Pengar], is published in Sweden in 1885. The two novels focus on young women having to find their identities within society’s new possibilities, as well as the new gender roles; developed by the new society. In their relations with both conventional and non-conventional male characters, the two female characters transgress society’s former established and given norms. In this article, the aim is to present how two female protagonists, the French Raoule and the Swedish Selma, are given different background conditions and qualities that finally can contribute to picture and explain their outstanding independence. Moreover, the new gender roles and their impact on the two female characters are discussed within themes and terms such as the "new woman", androgynity, sexuality and other explicite ingredients and symbols often discussed in a decadent context. Through the comparisons, this article shows how the two female portraits express the decadent transgressivity, in several aspects similarly, with individual voices, despite their two separate literary milieux.